Optimisation of minimal processing variables to preserve the functional quality and colour of carrot juice by means of the response surface methodology - Ferrario, Mariana Inés (2017)
Combined processes based on acidification (pH: 4.5, 5.0, 5.5) and mild thermal treatments (T: 56, 58, 60°C) at different exposure times (t: 2, 4, 6 min) were optimised using the response surface methodology to improve the functional quality of carrot juice. The effects on α- and β-carotenes, total antioxidant activity (TAA) and colour parameters were assessed. All combinations exhibited higher α- and β-carotenes than untreated juice due to an increase on the extractability during processing. T was the most influential factor increasing carotenes as T increased. Conversely, TAA was more affected by pH. The maximum TAA was observed at pH 4.5 at 56°C. Moreover, samples with the lowest pH were the most luminous with highest a* and b*. The combination of pH 4.5 at 60°C, 4 min simultaneously showed high carotenes and TAA, resulting a good alternative to improve the functional quality and colour of carrot juice.